Optimal group and individual prenatal care visit patterns and preterm birth - Moonseong Heo; Jessica L. Britt; Lu Zhang; Emily A. Doherty; Amy H. Crockett (BMC Pregnancy and Childbirth)
Abstract Background Changes have recently been proposed to both the visit frequency and setting for delivery of prenatal care, including decreasing frequency of scheduled visits or using group visits or virtual visits. The impacts of participant engagement patterns with prenatal care on preterm birth (PTB) are not clearly understood. We aimed to characterize prenatal care visit patterns, examine their associations with PTB, and provide optimal cutoffs for care patterns. Methods This study is a secondary analysis of prenatal care visit data obtained from the randomized CRADLE study that tested the effects of group (GPNC) versus individual (IPNC) prenatal care on PTB. We analyzed prenatal care visit data from N = 1,989 medically low-risk pregnant women who had at least one prenatal care visit between study enrollment and gestational age (GA) week 37. Prenatal care visit patterns before GA week 37 were predictors, characterized in terms of the number of IPNC and GPNC visits, duration of care, total hours of care, GA week at last visit, minimum gap (> 21 vs. ≤ 21 days) between any or GPNC visits, and discontinuation before the third trimester. PTB was the study outcome, defined as delivery < 37 GA weeks. Simple and multivariable logistic regression models and ROC analysis were applied to test associations and determine optimal cutoff points. Results Overall, > 7 visits during pregnancy (OR = 0.58, 95%CI: 0.43–0.79, p < .001), > 3 visits in the third trimester (OR = 0.42, 95%CI: 0.30–0.57, p < .001), > 2.25 care hours during pregnancy (OR = 0.67, 95%CI: 0.49–0.92, p = .014), > 0.75 care hours during the third trimester (OR = 0.50, 95%CI: 0.37, 0.67, p < .001), and > 147 days in care (OR = 0.41, 95%CI: 0.30–0.56, p < .001) were all significantly associated with lower PTB rates. A minimum care gap of > 21 days was associated with higher PTB (aOR = 2.87, 95%CI: 1.76–4.69, p < .001) and discontinuation of care before the third trimester was the strongest correlate of PTB (aOR = 12.6, 95%CI: 6.5–24.5), p < .001) in terms of aOR compared to that of all the other pattern variables. Conclusion Patient engagement with prenatal care providers, including both duration and frequency, was associated with reduced risk of PTB. Any proposed revision to the schedule or frequency of prenatal care which decreases patient contact with healthcare providers may risk worsening birth outcomes. Clinical trial registration This study was registered on December 20, 2015, at ClinicalTrials.gov ( www.clinicaltrials.gov , NCT02640638) with a title, A RCT of Centering Pregnancy on Birth Outcomes (CRADLE).